Analisis Pelaksanaan Program Kampung Tematik di Kampung Jamu Wonolopo Kota Semarang - Putri, Andini Nidia; Dewi, Diah Intan Kusumo (Teknik PWK (Perencanaan Wilayah Kota), 2024)
The Semarang City Government has made various efforts to improve the welfare of the community in a just and equitable manner. The Thematic Village Program is one of the flagship programs of the Semarang City Government in overcoming the problem of meeting basic needs, economic, social and environmental. Kampung Jamu, Wonolopo Village, is one of the villages that participated in implementing this Thematic Village program. The purpose of this study was to determine the implementation of the Thematic Village Program in Kampung Jamu, Wonolopo Village, Semarang City. The implementation of the Thematic Village program is based on the achievement of the goals and objectives of the Thematic Village program in Herbal Village. The method used in this study is a quantitative method with data collection techniques through questionnaires to members of the Thematic Herbal Village as many as 25 respondents. The analytical technique used in this research is descriptive analysis and scoring analysis. The results of the implementation of the Thematic Village program in the Herbal Village, Wonolopo Village, can be categorized as successful, with a final score of 2.71. The results of this study were obtained because the Thematic Village program in Kampung Jamu was in accordance with the goals and objectives of the Thematic Village program. The highest level of success is the indicator of being able to meet the needs of life with an average score of 2.76. This proves that the Thematic Village program has an effect on meeting the daily needs of the community, because it is very helpful, especially in fulfilling transportation, communication, and recreation facilities. But not so much on the indicator of employment with the lowest average score of 1.2. This proves that the existence of Thematic Villages in Kampung Jamu currently has no effect on increasing the number of workers as indicated by a percentage of 80%. Meanwhile, 20% of the people think that the Thematic Village only helps a little but cannot create jobs for the community.